Metal–Organic Gels Derived from Iron(III) and Pyridine Ligands: Morphology, Self‐Healing and Catalysis for Ethylene Selective Dimerization. Issue 9 (10th April 2019) - Li, Botian; Zhou, Xue; Liu, Xiangyun; Ye, Haimu; Zhang, Ying; Zhou, Qiong
Abstract: Metal‐organic gels showing potential application in catalysis have received much concern. In this work, we designed and synthesized two metal‐organic gels based on coordination between Fe III and pyridine ligands at room temperature. The gels were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to reveal their assembly structures and morphologies, and it was found the metal‐organic gel derived from di‐topic ligand was composed of three‐dimensional network of nanofibers, while the gel derived from tri‐topic ligand was constituted of sponge‐like structure with amorphous phase. Rheological analysis showed the gel consisting of nanofiber networks displayed self‐healing property. The gels were used as catalysts for selective ethylene dimerization, and the optimum catalysis results of the gel with nanofibers reached the maximal catalytic activity of 1.48×10 5  g/(mol Fe⋅h) with C4 yield more than 90 %, whereas the sponge‐like gel only gave 38 % C4 products at the same condition. The higher dimerization selectivity of the former Fe III gel was attributed to its regular assembly structure and lower steric hindrance of the surface metal sites. Due to its catalytic activity, high selectivity and preparation simplicity, the Fe III gel might be potentially applicable for the preparation of C4 α‐olefins. Abstract : Healing benefits : Iron(III) metal–organic gels were fabricated based on the self‐assembly of multi‐topic pyridine ligands and Fe III salt under mild condition, displaying two morphologies including network of nanofibers and sponge‐like structure. The gels showed distinct self‐healing capacities. The catalytic activity and selectivity in ethylene dimerization of the different gels were characterized and discussed and compared.